2019
DOI: 10.1186/s12943-019-0981-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Exosome-transmitted miR-128-3p increase chemosensitivity of oxaliplatin-resistant colorectal cancer

Abstract: BackgroundOxaliplatin resistance is a major challenge for treatment of advanced colorectal cancer (CRC). Both acquisition of epithelial-mesenchymal transition (EMT) and suppressed drug accumulation in cancer cells contributes to development of oxaliplatin resistance. Aberrant expression of small noncoding RNA, miR-128-3p, has been shown to be a key regulator in tumorigenesis and cancer development. However, its roles in the progression of CRC and oxaliplatin-resistance are largely unknown.MethodsOxaliplatin-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
195
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(196 citation statements)
references
References 56 publications
1
195
0
Order By: Relevance
“…38,39 Exosomes with miR-128-3p increase chemosensitivity of oxaliplatin in drug-resistant colorectal cancer. 40 Exosomedelivered nucleic acid and proteins partly facilitate the resistance of breast cancer. 41 Exosomes derived from HEK293 could deliver siRNA that target PKL-1 and reduce expression of PLK-1 in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Exosomes with miR-128-3p increase chemosensitivity of oxaliplatin in drug-resistant colorectal cancer. 40 Exosomedelivered nucleic acid and proteins partly facilitate the resistance of breast cancer. 41 Exosomes derived from HEK293 could deliver siRNA that target PKL-1 and reduce expression of PLK-1 in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-128-3p was demonstrated to inhibit glioma cell proliferation and differentiation through the IRS-1/PI3K/AKT signaling pathway [69]. Exosome-transmitted miR-128-3p could also exert its anticancer effect by increasing the chemosensitivity of oxaliplatin-resistant colorectal cancer [70]. However, as far as we know, there have been no reports about the specific role of miR-128-3p in the MSCs osteogenic differentiation and bone fracture healing process.…”
Section: Discussionmentioning
confidence: 99%
“…CircATP8B4 was demonstrated to promote glioma radioresistance by serving as a miR-766 sponge, and circATP8B4 in EVs may be a potential biomarker for glioma radioresistance. It was reported that exosome-transmitted miRNA may promote chemosensitivity in multiple cancer types such as colorectal cancer and head and neck cancer (124,125), and recent studies have revealed that circRNAs mediate chemotherapy resistance in various types of cancer such as ovarian cancer and thyroid carcinoma (126)(127)(128). Hence, there is a novel hypothesis that exosomal circRNAs are influence chemotherapy resistance, but this still requires further experimental confirmation (Fig.…”
Section: Exosomal Circrnas Promote the Generation Of Premeta-mentioning
confidence: 99%